Leaching of copper from Kupferschiefer by glutamic acid and heterotrophic bacteria. (1st May 2015) - Kostudis, Sophia; Bachmann, Kai; Kutschke, Sabine; Pollmann, Katrin; Gutzmer, Jens
Highlights: Leaching of Kupferschiefer using glutamic acid is feasible. The most prominent part in copper recovery is contributed by chalcocite. Covellite is formed during leaching. Abstract: Polymetallic Cu–Ag ores of the Central European Kupferschiefer deposits are one of the most important sources of copper in Europe. Because the ores are typically complex and often exceptionally fine-grained the development of efficient alternatives to conventional beneficiation strategies are an important target of current research. Biomining – the use of biological components for metal extraction – may offer solutions that are both efficient and environmentally benign. As conventional bioleaching with acidophilic microorganisms is impeded by the high carbonate content of the Kupferschiefer ores, heterotrophic microorganisms and glutamic acid are investigated as a possible alternative in the present study. The focus of this investigation is solely on the recovery of copper from the Kupferschiefer sensu strictu . Bioleaching experiments were carried out using such material from the Polkowice Mine in Poland. This material is marked by high grade (3.8 wt.% Cu), complex ore mineralogy (chalcocite, bornite, chalcopyrite and covellite in significant quantity) and a gangue mineralogy that is rich in carbonate, organic carbon and clay minerals that together form a very fine-grained matrix. (Bio)leaching experiments yield best results when glutamic acid alone is used – reaching copper recoveries up to 44%. Recoveries are consistently lower in experiments in which glutamic acid and microbiological metabolites are both present. The leaching of chalcocite renders the greatest contribution to the copper recovered to the leach solution in all experiments. It can be concluded that glutamic acid solubilises copper efficiently from Kupferschiefer, mainly from chalcocite.